(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Many studies affirm that there is a positive relationship between intellectual capital and the organizational performance of companies. However, there are few efforts to explain this relationship in higher education institutions in South America and none in Bolivia. To examine this great potential, a theoretical model has been developed and tested that explains how intellectual capital impacts the performance of the Universidad San Francisco Xavier de Chuquisaca. In this study, the scope of intellectual capital includes human capital, relational capital, and structural capital, and to measure organizational performance, the indicators proposed in the approach of the European Foundation for Quality Management (EFQM) have been considered. This research examines the results of the information obtained from key informants belonging to all the careers offered by the USFXCH. The PLS-SEM Structural Equations Model has been used. The results provide convincing support for the importance of intellectual capital management, specifying that human capital is directly related to structural and relational capital and the latter clearly influences performance in a public institution of higher education such as the USFXCH.